Final integration, commissioning and start of the Wendelstein 7-X stellarator operation. (3rd August 2017) - Bosch, H.-S.; Brakel, R.; Braeuer, T.; Bykov, V.; van Eeten, P.; Feist, J.-H.; Füllenbach, F.; Gasparotto, M.; Grote, H.; Klinger, T.; Laqua, H.; Nagel, M.; et al.
Abstract: The main objective of the Wendelstein 7-X (W7-X) stellarator is to demonstrate the integrated reactor potential of the optimized stellarator line. An important element of this mission is the achievement of high heating-power and high confinement in steady-state operation. Such an integrated plasma operation has not yet been demonstrated and represents the major scientific goal of W7-X. The way towards this goal is staged. In the first phase, called OP 1.1, December 2015-March 2016, a limiter configuration was used. In this paper, the preparation of the first operation phase as well as lessons learned during the first commissioning and the operation phase are discussed, while the physics results from OP 1.1 are reported elsewhere (Wolf et al 2017 Nucl. Fusion 57 102020).